Ag and Mn-doped mesoporous bioactive glass nanoparticles incorporated into the chitosan/gelatin coatings deposited on PEEK/bioactive glass layers for favorable osteogenic differentiation and antibacterial activity. Issue 5 (17th July 2020) - Nawaz, Aneeqa; Bano, Shaher; Yasir, Muhammad; Wadood, Abdul; Ur Rehman, Muhammad Atiq
Abstract : Multifunctional bioactive and antibacterial coatings for orthopedic applications. Abstract : Bioactive and antibacterial coatings were developed and characterized in this study. Chitosan/gelatin/Ag–Mn doped mesoporous bioactive glass nanoparticles (Ag–Mn MBGNs) composite coatings (of 5–6 μm thickness) were deposited using electrophoretic deposition (EPD) on PEEK/bioactive glass (BG) layers (of 60–70 μm thickness), which had been deposited by EPD onto stainless steel. The chitosan/gelatin/Ag–Mn MBGNs composite coatings deposited on PEEK/BG layers were optimized by the Taguchi design of experiment (DoE) approach; the resulting microstructure, composition, in vitro bioactivity, antibacterial activity, and cytocompatibility were investigated. Scanning electron microscopy (SEM) images confirmed the deposition of Ag–Mn MBGNs on the surface of PEEK/BG layers. Energy dispersive spectroscopy (EDX) confirmed the presence of Mn and Ag, which were embedded in chitosan/gelatin (top layer). The presence of BG particles in the PEEK/BG layer and Ag–Mn MBGNs in the top layer allows the multi-structured coatings to form apatite like crystals upon immersion in simulated body fluid (SBF). Moreover, the release of silver ions from the top layer provided an antibacterial effect against Escherichia coli and Staphylococcus carnosus .